Analisis Faktor-Faktor Yang Memengaruhi Perilaku Konsumtif Siswa Program Keahlian Akuntansi SMKN 1 Surabaya - Reysa Anggita Wahyudi; Rochmawati Rochmawati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
Consumptive is an activity of purchasing and using products or services in excess to obtain maximum satisfaction. This study intends to conduct testing and analysis of the factors of consumer behavior in the form of lifestyle, peer groups, self-control, and financial literacy. The research conducted is an associative type and uses quantitative methods. The population studied was all students of class X - XI Accounting skills program SMK Negeri 1 Surabaya, with a total sample of 90 students. The sampling technique is simple random sampling and the data collection is done using a questionnaire and tests. Data analysis was performed through the classical assumption test, multiple linear regression test, and hypothesis testing. The results obtained are: (1) Partial influence of lifestyle, peer groups, self-control, and financial literacy on consumer behavior is found; (2) The partial influence of lifestyle on the consumptive behavior of students positively and significantly; (3) The partial influence of peer groups on consumptive behavior positively and significantly; (4) The influence of self-control on students' consumptive behavior negatively and significantly; (5) There is no partial effect of financial literacy on consumer behavior.